The Rio Mata Cavalo group: The gold mineralization and its origin - Angeli, Nelson; Penha, Ulisses Cyrino; Knauer, Luiz Guilherme; Ito, Gabriel Mineo (My University, 2011)
The metavolcano-sedimentary sequences, at the southeastern of Espinhaço ridge, present difficulties for distinction of Rio das Velhas Supergroup, till now. Besides of very similarities it is possible to separate the Rio Mata Cavalo Group from the last one. It is constituted by metamafic-ultramafic unit derivated from tholeitic basalts, and a chemical-clastic cover. These sediments present gold and Platinum Group Minerals/Elements associated mainly with Banded Iron Formations. Hydrothermal origin is attributed to noble metals concentration. The prospecting and mineral exploration was done only for gold in the study area. The obtained results permit to suggest the use for an Upper Unit, composed by chemical-clastic sediments, and a Lower Unit, which comprises the volcanic rocks as belonging to Mata Cavalo Group. So, this Group presents in Upper Unit magnetite-rich BIF with gold associated to supergene enrichment.
O Grupo Rio Mata Cavalo: A mineralização de ouro e sua origem
Keywords: Gold mineralization; Hydrothermalism; Metavolcano-sedimentary sequence; Rio Mata Cavalo Group; Southeastern of Espinhaço Ridge